Pelatihan Pembuatan Multimedia Interaktif Berbasis Genially Pada Pembelajaran IPAS bagi Guru MI Plus Ja-Alhaq Kota Bengkulu - Yusnia; Debi Heryanto; Neza Agusdianita; Rizqa Dwi Shofiya Maghfira Izzania (IPI Press, 2026)
Science learning (IPAS) in Islamic elementary schools requires the visualization of abstract and integrative concepts, yet most teachers still face limited digital literacy in packaging such material attractively. Learning tends to be conventional and textbook-oriented, leading to student boredom. This community service program aims to improve teachers’ knowledge and skills in creating Genially-based interactive multimedia for IPAS learning. The method applied an observational and structured modeling approach operationalized into four phases: attention, retention, reproduction, and motivation. Data were collected through direct observation, documentation, and pretest posttest instruments. The evaluation results showed an increase in the average knowledge score from 70 to 90 and the average skill score from 73 to 94. This improvement confirms that training with structured modeling is effective in fostering teachers’ digital pedagogical competence while producing ready-to-use interactive media products. It is concluded that Genially training contributes significantly to the innovation of IPAS learning in madrasah and is recommended for sustainable dissemination to other Islamic elementary schools in Bengkulu City.